THE INFLUENCE OF BEETROOT (Beta vulgaris) ON SPERMATOZOA VITALITY OF WISTAR RATS EXPOSED TO MOSQUITO COILS - Bharadaksa, Mohammad Arya Lingga; Ariani, Mahayu Dewi; Dewi, Puspita Kusuma; Nugroho, Trilaksana (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Spermatozoa vitality is one of the sperm analysis test. Application mosquito coil repellentgenerates free radical enhancement. Free radical contribute to external factor thatinfluence the quality of spermatozoa vitality. Beetroot(Beta vulgaris) contain a considerably high amount of antioxidant. It reduce free radical in the body and improve quality of spermatozoa vitality. Aim: To find out and analyze the effect of beetroot (Beta vulgaris) on the spermatozoa vitality of male wistar rats exposed to mosquito coils. Methods: This research uses experimental methods, with a post-test only control group design. The research sample was selected using a simple random sampling technique28 male wistar rats met the inclusion and exclusion criteria, then divided into 4 treatment groups K (-), K (+), P1 and P2.Data obtained after 56 days of treatment with 7 days of adaptation before treatment, the data will be tested for normality with Shapiro-Wilk then proceed one way ANOVA if the data distribution is normal. Results: Shapiro-Wilk test showed no significant differences between groups K (-), K (+), P1 and P2 (p> 0.05). One way ANOVA test on sperm vitality analysis showed a significant difference between groups. Post-Hoc test showed sperm vitality on K (+) there was significant difference compared to K (-) (p <0.001), K (+) no significant difference compared to P1 (p = 0.244) and K (+) there was significant difference compared to P2 (p = 0.001). Conclusion: Giving beetroot juice with the right dose has a significant effect on the spermatozoa vitality of male wistar rats exposed to the smoke of mosquito coils.